Ballistic Impact Study of an Aramid Fabric by Changing the Projectile Trajectory - Larisa Titire; Cristian Muntenita (Fibers)
Personal protective systems widely use aramid textile fabrics, whether in soft or rigid form, to protect against various types of ballistic threats. Ballistic impact refers to a high-velocity impact caused by a thrusting source, often involving a low-mass object. To use these materials effectively in structural applications, it is crucial to have a thorough understanding of their ballistic behavior when subjected to high-velocity impact. Upon contact of the projectile with the ballistic material, complex ballistic penetration processes take place, which require a comprehensive and quantitative examination for a better understanding. This study aims to analyze the damage mechanism of aramid fabric by altering the projectile impact trajectory based on numerical simulations. We aim to obtain a thorough understanding of the behavior of the aramid fabric by performing numerical simulations and examining the penetration process in detail. The obtained results are analyzed based on the von Mises stress distribution (panel and projectile, projectile only, and main wires), projectile deformation, projectile velocity during ballistic impact, and based on photographs obtained during the impact.